Ten Years Road Maintenance Activity and Forecast: A Case Study - Afifa Anuar, Siti; Syahirah Jamaludin, Syazana; Hamsan, Raziff (International Journal of Engineering and Technology, 2026)
This paper discusses the result of a research activity on forecasting activities as well as related financial requirement in maintaining state roads in a single local district. This forecasting is based on Pavement Condition Assessment (PCA) conducted on routes in this district, and then data was analyzed. Current practice of road maintenance does not allow local authority to project the financial requirement in maintaining the roads, as corrective actions are taken based on report and scheduled maintenance check. Hence, the condition of the road will deteriorate further and this may affect the socio-economics of the surrounding areas. For this situation, preventive maintenance will be a viable solution. With this, a method was developed to forecast 10 years of maintenance works and financial requirement. The steps taken to design this model are through pavement condition assessment (PCA) where the analysis were done. The result produces a 10 year forecast of the financial requirement for the purpose of road maintenance in the district. Based on analysis a total of RM 21.27 million is required in a span of 10 years, where 35% of the total amount is needed in the first year for corrective maintenance works.